Reconstruction Of Legal Policy On Decency Crime In Indonesia Based On Pancasila Value (LGBT Rehabilitation Institute For Children) - Cucuk Kristiono (Universitas Islam Sultan Agung, 2019)
YKPN survey results showed that there are about 4000-5000 gay in Jakarta. Gaya Nusantara estimates there are 260.000 of the 6 million residents of East Java is Gay. Gays registered as members of the gay community in Indonesia there are 76.288. While Oetomo estimate, there is 1% of the Homosexual community in Indonesia. Connecting with LGBT victims rehabilitation treatment in children by agency or entity that has not been regulated in Article 292 of the Criminal Code following criminal sanctions if not carried out rehabilitation. Juridical empirical approach is used in hopes obtained a clear and complete picture of the background and the ins and outs of why the implementation of the children rehabilitation of LGBTâ€™s victims urgent to be done and set in article 292 of the Criminal Code in the form of additional verse. Considering article 292 of the Criminal Code did not regulate and discusses how the continuation of children as LGBTâ€™s victim and only focus on criminal prosecution against the perpetrators only. This sort of thing happens because the regulations have not explicitly regulate this issue. LGBT in Indonesia, including the diversion of moral and immoral acts in the category, but in the regulation of fixed elements deemed equal before the law properly human. Because justice remains true for all citizens with regard to the Pancasila values.Keywords: Reconstruction; Rehabilitation; LGBT; Children; Pancasila Value.Â